Laparoscopic cholecystectomy in patients with COVID–19 and in a postcovid period - V. V. Mіshchenko; P. І. Pustovoit; R. Yu. Vododiuk; V. V. Velichko (Клінічна хірургія, 2021)
Objective. Determination of the role and place for laparoscopic cholecystectomy on background of COVID-19 and in postcovid period.